The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ggge.20212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the inter tropical discontinuity on Harmattan dust deposition in Ghana

Abstract: [1] The Harmattan is a dry dust-laden continental wind, and in the boreal winter Harmattan dust plumes affects many West African countries, including Ghana. When the Harmattan is strongest the southern part of Ghana is affected by the Inter Tropical Discontinuity (ITD). In this study, we investigate if the ITD functions as a barrier, preventing long transported Harmattan dust to settle south of, and below, it. This is done by analyzing a Harmattan dust outbreak, mapped using Earth observation (EO) data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The study by Kim et al (2017) further noted the role of surface wind and vegetation cover in multi-decadal variations of dust emission in the Sahara and Sahel and their findings suggest Saharan-Sahelian winds system as the main driver of inter-annual variation of dust emission. However, the influence of the ITD on Harmattan dust deposition has been observed by Lyngsie et al (2013) in Ghana and their result revealed various effects of ITD on dust deposition during the Harmattan period. The major difference between their findings and that of this study is that Lyngsie et al (2013) only examined the dust deposition during the Harmattan without considering the variation in the AOD over different seasons of the year, which is the major contribution of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Kim et al (2017) further noted the role of surface wind and vegetation cover in multi-decadal variations of dust emission in the Sahara and Sahel and their findings suggest Saharan-Sahelian winds system as the main driver of inter-annual variation of dust emission. However, the influence of the ITD on Harmattan dust deposition has been observed by Lyngsie et al (2013) in Ghana and their result revealed various effects of ITD on dust deposition during the Harmattan period. The major difference between their findings and that of this study is that Lyngsie et al (2013) only examined the dust deposition during the Harmattan without considering the variation in the AOD over different seasons of the year, which is the major contribution of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of the ITD on Harmattan dust deposition has been observed by Lyngsie et al (2013) in Ghana and their result revealed various effects of ITD on dust deposition during the Harmattan period. The major difference between their findings and that of this study is that Lyngsie et al (2013) only examined the dust deposition during the Harmattan without considering the variation in the AOD over different seasons of the year, which is the major contribution of this study. However, the results from this study revealed the influence of ITD on seasonality of AOD, on a continuous basis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is unclear as the bed rock is probably metamorphic or igneous (African shield). There may be local depositional features, or other possibilities include heavy cation deposition from Saharan dust, transported from the Bodele Depression (the basin of Lake Chad in the southern edge of the Sahara Desert) during the Harmattan winds in January and February (Lyngsie, Olsen, Awadzi, Fensholt, & Breuning‐Madsen, ; Tiessen, Hauffe, & Mermut, ; Washington, Bouet, & Cautenet, ). The soil texture at the DF and WS sites is very sandy with low water and nutrient retention capacity, whereas the SDF and EF sites have loamy soils.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the combination of the ITD and the presence of orography can lead to dry cyclogenesis and subsequent dust emissions over the Sahel (Bou Karam et al, 2009b). The role of the ITD on dust activities has also been noted by, for example, Knippertz (2008) and Lyngsie et al (2013), and more recently by Francis et al (2020b) on its contribution to the historical dust storm of June 2020 that extended into the tropical Atlantic Ocean and North America. Odekunle (2010) and Odekunle and Adejuwon (2017) reported on the effects of the ITD on the variability of the precipitation regimes in Nigeria.…”
Section: Introductionmentioning
confidence: 97%